MODELLING AND ENERGY STORAGE MANAGEMENT SYSTEM FOR HYBRID ELECTRIC VEHICLES WITH FUZZY LOGIC CONTROLLER AND PMSM DRIVE (International Journal of Food and Nutritional Sciences, 2021)
Automobile power systems are increasingly in need of renewable energy resources. However, the conventional mechanisms failed to provide better energy management system (EMS) performance. Therefore, this article is focused on implementation of hybrid EMS system using solar photo voltaic (PV), fuel cells, super capacitor and battery storage system for permanent magnet synchronous machine (PMSM) drive of hybrid electrical vehicle with fuzzy logic controller (FLC). The PV fuel cell hybrid electrical vehicle is a model-based approach and delivers two major original contributions. A fuzzy logic control-based energy management strategy. Super capacitors and battery storage systems are used for rapid charging and different levels of battery state of charge.The power systems prove to work effectively and adaptively in different situations under the regulation of the EMS and demonstrate better fuel economy than using a widely-adopted power-following control strategy. The simulations conducted using Matlab/Simulink model showed that the proposed method outperformed as compared to state-of art approaches